Activation of 1-Aminocyclopropane-1-Carboxylic Acid Synthases Sets Stomatal Density and Clustered Ratio on Leaf Epidermis of Arabidopsis in Response to Drought - Jia, Ming-zhu; Liu, Ling-yun; Geng, Chen; Jiang, Jing (Frontiers in Plant Science, 2021)
The adjustment of stomatal density and clustered ratio on the epidermis is the important strategy for plants to respond to drought, because the stoma-based water loss is directly related to plant growth and survival under drought conditions. But the relevant adjustment mechanism still needs to be explored. 1-aminocyclopropane -1-carboxylate (ACC) is disclosed to promote stomatal development, while in vivo ACC levels depend on activation of ACC synthase (ACS) family members. Based on the findings of ACS expression involving in drought response and several ACS activity inhibitors reducing stomatal density and cluster in drought response, here we examined how ACS activation is involved in the establishment of stomatal density and cluster on the epidermis under drought conditions. Preliminary data indicated that activation of ACS2 and/or ACS6 (ACS2/6) increased stomatal density and clustered ratio on the Arabidopsis leaf epidermis by accumulating ACC under moderate drought, and raised the survival risk of seedlings under escalated drought. Further exploration indicated that, in Arabidopsis seedlings stressed by drought, the transcription factor SPEECHLESS (SPCH), the initiator of stomatal development, activates ACS2/6 expression and ACC production; and that ACC accumulation induces Ca2+ deficiency in stomatal lineage; this deficiency inactivates a subtilisin-like protease STOMATAL DENSITY AND DISTRIBUTION 1 (SDD1) by stabilizing the inhibition of the transcription factor GT-2 Like 1 (GTL1) on SDD1 expression, resulting in an increases of stomatal density and cluster ratio on the leaf epidermis. This work provides a novel evidence that ACS2/6 activation plays a key role in the establishment of stomatal density and cluster on the leaf epidermis of Arabidopsis in response to drought.